PENGARUH KOMPLEKSITAS TUGAS, TEKANAN KETAATAN, PENGALAMAN AUDITOR, DAN INDEPENDENSI TERHADAP AUDIT JUDGEMENT - Muhammad Iqbal (2017)
This study aims to test and to obtain empirical evidence about the influence of Task Complexity, Pressure of Obedience, Experience Auditor, and Independence of Judgment Audit. The population in this study amounted to 10 KAP in South Jakarta area. The sample in this study using purposive sampling, with the criteria of respondents registered in the Public Accounting Directory by IAPI. Data collection based on questionnaires were distributed as many as 75 questionnaires, but only 57 were returned and only 54 were processed. Data analysis using multiple linear regression. The results of this study indicate that the Task Complexity has significant effect on Judgment Audit, but the Obedience Pressure, Auditor Experience, and Independence have no significant effect on Audit Judgment.